A rare finding of giant accessory mitral valve tissue: a case report. Issue 1 (31st January 2020) - Okafor, Joseph; Kanaganayagam, Gajen Sunthar; Patel, Ketna
Abstract: Background: Accessory mitral valve tissue (AMVT) is a rare anomaly that can be detected in the first decade. It is associated with other congenital cardiac abnormalities, such as ventricular septal defect. When detected in adulthood, it is usually an incidental finding on echocardiography. Symptomatic individuals can present with breathlessness, syncope, and features of distal tissue embolization. Cardiac surgery is indicated in those with significant left ventricular outflow tract obstruction. Case summary : A 45-year-old man without any significant medical history was referred due to an abnormal electrocardiogram. He was asymptomatic from a cardiac perspective. Echocardiography revealed the presence of a giant mobile mass attached to the anterior mitral valve leaflet and prolapsing into the left ventricular outflow tract (LVOT). This was classified as Type IIB2 AMVT. As there was no dynamic outflow tract obstruction on subsequent treadmill stress echocardiography, and in the absence of other coexistent congenital abnormality, surgical excision was not performed. Discussion : It is important to exclude significant obstruction when a large AMVT is seen to be prolapsing into the LVOT. Three-dimensional echocardiography is the tool of choice for anatomical classification and to assess for concomitant congenital cardiac abnormalities.